Mathematical modelling of molecule evolution in protocells - Myszor, Dariusz; Cyran, Krzysztof A. (Zielona Góra: Uniwersytet Zielonogórski)
In this article, we analyse the process of the emergence of RNA polynucleotides located in an enclosed environment, at an early stage of the RNA world. Therefore we prepared a mathematical model, composed of a set of differential equations, which simulates the behaviour of an early biological system bounded by a protocell membrane. There is evidence that enclosed environments were available on the primordial Earth. There are also experimental proofs that RNA strands can develop in these formations.
Keywords: RNA world; proto-cell; mathematical model